Health promoting schools as learning sites for physicians in‐training. Issue 3 (2014) - ,; ,; ,; ,; ,
Abstract : Purpose – Although medical schools do well in preparing the next generation of practitioners to diagnose and clinically treat illness, they struggle in preparing them with capabilities in the areas of health promotion and disease prevention. Similarly, health promoting schools (HPS) face challenges in working to enhance the health and educational outcomes of children. The paper aims to discuss these issues.Design/methodology/approach – The authors draw from their local and international collaborative work as practitioners and medical educators to examine how health professions schools can work in partnership with HPS for mutual benefit.Findings – Health advocacy is a core competency in medical education. A primary focus is on health promotion and disease prevention. However, providing practical, experiential opportunities – "learning‐by‐doing" – is a challenge. To overcome this difficulty, medical schools may be well served by partnering with HPS. This can provide mutually beneficial learning opportunities that will enable emerging physicians to develop health promotion‐related knowledge and advocacy skills while the emerging generation of citizens (the children) are enabled to live healthier and more productive lives.Originality/value – The parallel development of Health Promoting Schools and the teaching of health advocacy to health professionals has proceeded to the point where convergence of the gathered knowledge and experience can provide a powerful and synergistic model to advance both initiatives. This conceptual paper focuses outlines the actions that might achieve this. Acknowledgements : The authors gratefully acknowledge funding support for the "International Colloquium Abroad" hosted by the Stellenbosch Institute for Advanced Study, Stellenbosch University, South Africa from the Peter Wall Institute of Advanced Studies at the University of British Columbia.